RETRACTED ARTICLE: Effect of miR-181a-3p on osteogenic differentiation of human bone marrow-derived mesenchymal stem cells by targeting BMP10 - GuiLu Tao; Ping Mao; HaoNan Guan; MinFei Jiang; Tongbin Chu; CunDi Zhong; JiaZheng Liu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:GuiLu Tao, Ping Mao, HaoNan Guan, MinFei Jiang, Tongbin Chu, CunDi Zhong & JiaZheng Liu (2019) Effect of miR-181a-3p on osteogenic differentiation of human bone marrow-derived mesenchymal stem cells by targeting BMP10. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 4159–4164, DOI: 10.1080/21691401.2019.1687494Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to verify their original data or answer our questions about research ethics and the informed consent process. It has also come to our attention that the full authorship list and affiliations for this manuscript were changed between submission and acceptance. As determining authorship is core to the integrity of published work and given our concerns regarding the data and ethics approvals, we are therefore retracting this article and the corresponding author listed in this publication has been informed.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.